Eco-innovation as a pillar for sustainable development of circular economy - Jelena Stankevičienė; Marta Nikanorova (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Circular economy (CE) is based on environmental, economic and social dimensions which aim to ensure sustainable development on each step of product creation, transformation and conversion by creating a closed-loop economy. The purpose of the article is to propose a concept of measurement the development of eco-innovations in the context of circular economy, apply and provide empirical evidence based on the data of Baltic Sea Region countries. The study augmented for the models that include the analysis of the circular economy concept, the importance of eco-innovation in the context of circular economy including the accent on recycling, circular material usage, material efficiency and waste management. The multi-criteria decision methods MULTIMOORA and TOPSIS were used to assess the eco-innovation as a pillar of circular economy. Results are useful to add to theoretical building and also evaluate the socio-economic aspect in the concept of circular economy.
Keywords: D07; O11; O44; O52; 650; circular economy; sustainable development; eco-innovation; MULTIMOORA; TOPSIS